1998
DOI: 10.1182/blood.v91.5.1742
|View full text |Cite
|
Sign up to set email alerts
|

Differential Induction of Apoptosis by Fludarabine Monophosphate in Leukemic B and Normal T Cells in Chronic Lymphocytic Leukemia

Abstract: Fludarabine (F-ara-A), an adenine nucleoside analog with efficacy in B-cell chronic lymphocytic leukemia (B-CLL), has also been shown to have a long-lasting suppressive effect on T lymphocytes. In heterogeneous clinical samples, apoptosis cannot be detected by standard methods in small cellular subsets. We developed, therefore, a combined assay of in situ end-labeling of nicked DNA by terminal deoxynucleotide transferase, with measurements of cellular DNA content and surface antigens (CD3, CD4, CD8, and CD19) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(16 citation statements)
references
References 22 publications
3
13
0
Order By: Relevance
“…In our study, comparable results were obtained on leukaemic B lymphocytes. The apoptotic effect of HCQ was observed early at 1 h after treatment compared with others drugs, such as fludarabine, in which significant apoptosis was not noted for a few days (Consoli et al, 1998). The HCQ-induced apoptosis of B-CLL cells involves the activation of caspase-3, as previously described for glucocorticoid-, fludarabine-, and mitoxantrone-induced apoptosis (Bellosillo et al, 1997;Chandra et al, 1997;Stoetzer et al, 1999).…”
Section: Discussionsupporting
confidence: 59%
“…In our study, comparable results were obtained on leukaemic B lymphocytes. The apoptotic effect of HCQ was observed early at 1 h after treatment compared with others drugs, such as fludarabine, in which significant apoptosis was not noted for a few days (Consoli et al, 1998). The HCQ-induced apoptosis of B-CLL cells involves the activation of caspase-3, as previously described for glucocorticoid-, fludarabine-, and mitoxantrone-induced apoptosis (Bellosillo et al, 1997;Chandra et al, 1997;Stoetzer et al, 1999).…”
Section: Discussionsupporting
confidence: 59%
“…These data are in agreement with those of Vermes et al (1997), who similarly reported no real increase in apoptosis among CLL cells. Consoli et al (1998) confirmed this concept by evaluation of fludarabine‐induced apoptosis. Using the in situ end labelling technique, these authors found a higher percentage of cells with DNA strand breaks associated with apoptosis in normal CD19 + B cells compared with CLL cells or other lymphocyte subpopulations.…”
Section: Discussionsupporting
confidence: 53%
“…Based on the clinical evidence that CLL is characterized by the accumulation of long‐lived lymphocytes, several studies have investigated whether apoptosis of CLL cells could play a role in the disease (Collins et al , 1989; Hanada et al , 1993; Aguilar‐Santelises et al , 1994; Robertson et al , 1996; Binet et al , 1996; Pepper et al , 1997; Consoli et al , 1998). The involvement of survival regulators, such as cytokines and soluble molecules has also been extensively evaluated in CLL (for a review see Orsini et al , 2000).…”
mentioning
confidence: 99%
“…Other enzyme targets of F-AraA include DNA primase, DNA polymerase a, DNA ligase, and DNA topoisomerase II (Tseng et al, 1982). Thus, the mechanism of action of F-AraA in proliferating cells is mainly cell cycle specific, and incorporation of F-AraA into DNA during S phase is required for the induction of apoptosis (Consoli et al, 1998;Galmarini et al, 2001Galmarini et al, , 2002. In nondividing cells, the inhibition of cellular DNA repair is the most likely explanation for cytotoxicity of F-AraA and CdA.…”
Section: Deoxyribonucleoside Analoguesmentioning
confidence: 99%